Data backup methods for mission-critical information systems - S. V. Shaytura; P. N. Pitkevich (Российский технологический журнал)
Objectives. Digitalization of the economy has led to a situation in which organizations accumulate huge amounts of digital data, the loss or damage of which leads to irreparable damage to the organizations. The issue of increasing data safety is relevant. One of the ways to improve the safety of data is backing them up. The study aimed to develop an effective strategy for backing up data for critical enterprise information systems.Methods. The method for solving the problem was to create backup copies of enterprise information systems using a flexible architecture based on the backup—as a service in external cloud structures—in combination with technical resources of the organization.Results. This article discussed backup solutions and tools, which include: backup volumes and schedule, target point and recovery time. The strategies and mechanisms of data backup were analyzed. The most common backup mechanisms are removable media, backups, external hard drive, hardware, backup software, cloud backup services. To create backups on a network, a large external hard drive is created and archival software is used to save changes to local files on that hard drive. This article covered: backup strategy, concept of backup storage, different types of backup storage methods, including network storage, external hard drives, and cloud storage. The main provisions and rules for backing up critical information systems were described. The rules for copying servers were given.Conclusions. This article discusses a data backup architecture for mission-critical enterprise information systems. The authors believe that there should be at least three backups, two of which are located in the “cloud.” The 3–2–1 strategy developed by the authors gives quite satisfactory results for the safety of critical data.